Transcendence In Sasak Tarekat Literature: A Stylistic Analysis - Aswandikari Aswandikari; Sukri Sukri; Burhanuddin Burhanuddin; Syaiful Musaddat; Suhaib Al Faruq; Muhammad Sastrawan Barmansyah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This research is important to conduct because (1)